ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN BIOLOGI PADA KELAS X SMA NEGERI 1 GOMO - Harita, Kevin Briajun (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
Learning difficulties or learning disabilities, also known as learning disorders or learning disabilities, are disorders that make it difficult for the individual concerned to carry out learning activities effectively. The factors that cause learning difficulties are not easy to determine because these factors are complex. This research aims to analyze students' learning difficulties in learning biology in class X SMA Negeri 1 Gomo for the 2022/2023 academic year. The approach used in this research is to use a qualitative approach with a type of descriptive research that describes existing data, analyzes and interprets it. The research results that researchers obtained when carrying out research activities were as follows: the completeness of school facilities was still incomplete regarding biology subjects and most students found it difficult to learn scientific language so that this could result in students still getting grades above the KKM. The conclusion of this research is that: Based on the results of the research and discussion discussed in the previous chapter, the conclusion of this research is that students experience several difficulties in participating in teaching and learning activities in the classroom, especially in Biology subjects, such as laboratory rooms. not available, microscopes, projectors and several other facilities that support these learning activities. The reason why students find it difficult to learn scientific language is that students are less interested in studying and the books or teaching materials used only focus on one book, namely books published in the 2013 curriculum, so that students' involvement in learning is not fully able to follow it well. Based on the results of this research, the suggestion in this research is the need for school principals and related agencies to provide complete school facilities and infrastructure to support the continuity of learning activities well.